2018
DOI: 10.1175/jpo-d-18-0059.1
|View full text |Cite
|
Sign up to set email alerts
|

Deep Intraseasonal Variability in the Central Equatorial Atlantic

Abstract: Besides the zonal flow that dominates the seasonal and long-term variability in the equatorial Atlantic, energetic intraseasonal meridional velocity fluctuations are observed in large parts of the water column. We use 15 years of partly full-depth velocity data from an equatorial mooring at 23°W to investigate intraseasonal variability and specifically the downward propagation of intraseasonal energy from the near-surface into the deep ocean. Between 20 and 50 m, intraseasonal variability at 23°W peaks at peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…On intraseasonal timescales, variability in the equatorial Atlantic is dominated by TIWs in the western and central part and by wind-driven waves in the east (Athie and Marin, 2008). These waves significantly contribute to the upper-ocean heat and freshwater budgets through their influence on horizontal and vertical mixing (Foltz et al, 2003;Jochum et al, 2004;Hummels et al, 2013) and provide energy to EDJs via downward propagating Yanai beams (Tuchen et al, 2018). Moreover, there is evidence that mesoscale ocean dynamics significantly affect the tropical Atlantic Ocean and overlying atmospheric variability across a large range of time scales from daily to interannual and interdecadal (Seo et al, 2007;Chelton and Xie, 2010).…”
Section: Ocean Circulationmentioning
confidence: 99%
“…On intraseasonal timescales, variability in the equatorial Atlantic is dominated by TIWs in the western and central part and by wind-driven waves in the east (Athie and Marin, 2008). These waves significantly contribute to the upper-ocean heat and freshwater budgets through their influence on horizontal and vertical mixing (Foltz et al, 2003;Jochum et al, 2004;Hummels et al, 2013) and provide energy to EDJs via downward propagating Yanai beams (Tuchen et al, 2018). Moreover, there is evidence that mesoscale ocean dynamics significantly affect the tropical Atlantic Ocean and overlying atmospheric variability across a large range of time scales from daily to interannual and interdecadal (Seo et al, 2007;Chelton and Xie, 2010).…”
Section: Ocean Circulationmentioning
confidence: 99%
“…This signal is compatible with high baroclinic mode or vertically propagating Yanai waves (Figure 15). It can be related to the downward propagation of TIWs, as evidenced from mooring observations in the Atlantic Ocean (e.g., Bunge et al., 2008; Tuchen et al., 2018; Von Schuckmann et al., 2008). The TIWs in the equatorial Pacific are also associated with periods of 17 days (Lyman et al., 2007).…”
Section: Summary and Discussionmentioning
confidence: 90%
“…Deeper observations down to 3,000 m (e.g., Bunge et al., 2008; Tuchen et al., 2018, in the Atlantic, Eriksen & Richman, 1988, in the Pacific) also revealed the presence of intra‐annual variability. This variability has been related to the downward propagation of mixed Rossby‐gravity waves possibly generated by TIWs (Tuchen et al., 2018). In addition, in the equatorial Pacific Ocean, Farrar and Durland (2012) have noted the presence of variability of surface dynamic height relative to 500 dbars, in the period range 5–15 days, associated with inertia‐gravity and mixed Rossby‐gravity waves.…”
Section: Introductionmentioning
confidence: 93%
“…Correspondingly, the period of the second barocinic mode is 234 days (Table ) somewhat shorter than the dominant period of wind forcing. It should be noted that the wave energy Ē contains not only the annual signals but also the semiannual and seasonal signals in both the second and third baroclinic modes especially in the eastern equatorial Atlantic (Figures c–f) (Brandt et al () and Tuchen et al () have decomposed the moored zonal velocity data at 23°W obtaining energy spectra of various frequencies in different modes. They found that semiannual wave energy is more concentrated in the second baroclinic mode while highest annual wave energy appears in the fourth baroclinic mode.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it is possible to extend the AGC17 scheme into the vertical direction as well. Then recent problems associated with the oscillation of equatorial deep jet and velocity variability at different deep levels can be verified (Claus et al, ; Hua et al, ; Tuchen et al, ).…”
Section: Discussionmentioning
confidence: 98%